Diptera and Drosophila Karyotype Databases: A Useful Dataset to Guide Evolutionary and Genomic Studies - Morelli, Magnolia W.; Blackmon, Heath; Hjelmen, Carl E. (Frontiers in Ecology and Evolution, 2022)
Karyotypes and chromosome data have been widely used in many subfields of biology over the last century. Unfortunately, this data is largely scattered among hundreds of articles, books, and theses, many of which are only available behind paywalls. This creates a barrier to new researchers wishing to use this data, especially those from smaller institutions or in countries lacking institutional access to much of the scientific literature. We solved this problem by building two datasets for true flies (Order: Diptera and one specific to Drosophila), These datasets are available via a public interactive database that allows users to explore, visualize and download all data. The Diptera karyotype databases currently contain a total of 3,474 karyotype records from 538 publications. Synthesizing this data we show that several groups exhibit far greater variation in chromosome number and sex chromosome systems than others. These clades are of particular interest for future investigations by whole genome sequencing that could reveal the characteristics that lead to lability in genome structure.